Development of Air Temperature Measurement Using LM35 Sensor Based on Nodemcu Microcontroller and Internet of Things (IoT) - Nurcahya, Mufid Eska; Fianti, Fianti; Yulianti, Ian (Universitas Negeri Semarang, 2021)
The purpose of this research is to develop a real-time temperature monitoring instrument based on the Internet of Things (IoT). The research steps were design of a series of tools consisting of a Nodemcu microcontroller and an LM35 sensor, developing a tool that has been designed, testing the tool, and evaluating it. Performance analysis of the tool was carried out by measuring the relative error of the tool that has been developed with a standard thermometer. The result showed that the instrument's accuracy is 99.96% and the relative error percentage is 0.71%. It can be concluded that a room temperature measurement instrument with an IoT-based LM35 sensor can work well.